Insisting on a non-negative price: oligopoly, uncertainty, welfare, and multiple equilibria - Johan Lagerlöf (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
I study Cournot competition under incomplete information about demand while assuming that market price must be non-negative for all demand realizations. Although this assumption is very natural, it has only rarely been made in the earlier literature. Yet it has important economic consequences: (1) multiple (symmetric, pure strategy) equilibria can exist, despite the fact that demand and cost are linear; and (2) expected total surplus can be larger when the firms do not know demand than when they do, a result which has important implications for the social desirability of information sharing. The arguments of the paper are relevant also for price competition and for uncertainty about, e.g., cost or the number of firms, and these issues are discussed. – – In diesem Beitrag wird Cournot-Wettbewerb bei unvollständiger Information über die Nachfrage untersucht und unterstellt, daß der Marktpreis für alle Realisierungen der Nachfrage nichtnegativ ist. Obgleich diese Annahme sehr selbstverständlich ist, ist sie nur selten in der früheren Literatur verwendet worden. Dennoch hat sie wichtige ökonomische Konsequenzen: (1) können multiple Gleichgewichte existieren (symmetrisch, bei reinen Strategien), obwohl Nachfrage und Kosten linear sind; und (2) kann erwarteter Gesamtüberschuß größer sein, wenn die Unternehmen die Nachfrage nicht kennen als im Falle sie ihnen nicht bekannt ist. Dieses Ergebnis hat wichtige Implikationen für die soziale Erwünschtheit der gemeinsamen Nutung von Information (Information sharing“). Die Argumente des Beitrags sind auch für Preiskonkurrenz und für Ungewißheit beispielsweise hinsichtlich der Kosten oder der Zahl von Unternehmen relevant. Sie werden abschließend besprochen.
Keywords: D42; D43; D80; L12; L13; L40; 330; Non-negativity constraint; Multiple equilibria; Value of information; Information sharing; Trade associations; Antitrust policy